COVID-19 associated transverse myelitis: case report - Claudia V. Tapia-Fonseca; Omar D. Cortés-Enríquez; Laura P. Raya-Garza; Diana M. Gutiérrez-Cuellar (Permanyer, 2024)
Background: Transverse myelitis (TM) is a demyelinating inflammatory disease that presents with motor, sensory, and autonomic dysfunction, which may be acute or subacute. COVID-19-associated TM has been described in a scarce number of patients. Clinical case: A 15-year-old previously healthy male patient with respiratory disease before his neurological deterioration presented to the emergency room after developing a complete medullary syndrome located at the cervical-dorsal level, with ascending and symmetric paraparesis that rapidly progressed to paraplegia, with sensory dysfunction from the T3 level, sphincter dysfunction and sudden ventilatory deterioration that required mechanical ventilation. Magnetic resonance imaging was compatible with acute TM. Inflammatory and non-inflammatory etiologies were discarded. In addition, a positive severe acute respiratory syndrome coronavirus 2 test was obtained. Treatment included steroid pulses and plasmapheresis, with an insidious evolution. Conclusion: COVID-19 is an infrequent cause of TM and should be suspected when other etiologies have been ruled out.